Two new Phyllachora species in Southwest China - Li, Jin-Chen; Wu, Hai-Xia; Song, Jia-Yu (Phytotaxa, 2023)
Phyllachora species are biotrophic, obligate plant parasitic fungi featuring a high degree of host specificity, a high degree of species richness, and worldwide distribution. In this study, two Phyllachora species were collected from different hosts in Yunnan province, China. Based on morphological characteristics and multigene (LSU, ITS, SSU) phylogenetic analyses, they are introduced as two new taxa. Photographs, detailed descriptions, and notes are provided.